ANALYZING BINARIES AND BOUNDARIES IN AMITAV GHOSH’S THE SHADOW LINES - Banerjee, Abhisek (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper delves into the intricate interplay of binaries and boundaries within the novel. Amitav Ghosh masterfully explores the fluidity of identity and the arbitrary nature of borders, both physical and psychological. Through a fragmented narrative that intertwines personal and historical timelines, Ghosh challenges the reader to reconsider the distinctions between reality and imagination, past and present, and self and other. The novel’s structure, divided into “Going Away” and “Coming Home,” reflects the blurred lines between these concepts, as characters navigate their identities amidst shifting political and social landscapes. The protagonist’s journey, marked by his identification with his mentor Tridib and his eventual union with May, underscores the theme of interconnectedness that transcends geographical and temporal boundaries. The metaphor of ‘shadow lines’ serves as a powerful symbol of the illusory divisions that separate people and places, highlighting the shared human experiences that unite them. By examining the characters’ struggles with displacement, memory, and belonging, this paper aims to shed light on Ghosh’s critique of nationalism and the concept of fixed identities. The analysis will focus on how the novel’s fragmented structure and narrative techniques underscore the interconnectedness of individual lives and broader socio-political contexts. Ultimately, this paper argues that The Shadow Lines asserts the transformative power of imagination in transcending the limitations imposed by arbitrary boundaries, offering a nuanced perspective on identity, and belonging in a postcolonial world.